PENGARUH DUKUNGAN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING (Studi pada Koperasi Mitra Dhuafa Regional K Jawa Timur) - Apriliani, Shita Devi; Wati, Intan Ratna (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to analyze how much influence organizational support has on organizational citizenship behavior (OCB) with organizational commitment as an intervening variable in employees of Mitra Dhuafa Regional Cooperative K East Java. This study uses primary data through sending a research questionnaire link to permanent employees of Mitra Dhuafa Regional K Cooperative in East Java as a research sample, and secondary data through journals, books, and relevant data obtained from the company concerned. The data analysis technique uses Partial Least Square (PLS) with the help of the SmartPLS 3.0 application to test the hypothesis and the influence of the relationship between variables. This study involved 100 respondents who were taken with accidental sampling technique. The results of this study indicate that organizational support has a significant positive effect on organizational citizenship behavior (OCB), organizational support has a significant positive effect on organizational commitment, and organizational commitment also has a significant positive effect on organizational citizenship behavior (OCB). This study also shows the effect of organizational commitment as an intervening variable between organizational support and organizational citizenship behavior (OCB).